2017
DOI: 10.1590/s1806-92902017000700006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus buchneri inoculation or 1-propanol supplementation to corn silage on the performance of lactating Holstein cows

Abstract: -The objective was to evaluate the effects of corn silage supplemented with 1-propanol or inoculated with L. buchneri on the ruminal fermentation profile, digestibility, and production traits of lactating Holstein cows. Whole-corn plants were harvested at 350 g/kg dry matter (DM) and packed in nine bag silos (13 t/silo). At ensiling, two treatments were applied: control (no additive; six silos) and L. buchneri inoculation with 1 × 10 5 cfu/g (three silos). Feeding started after 247 days of storage; one L. buch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…The effects of feeding silage treated with LB on performance of dairy cows in the literature have been inconsistent. Although some studies have observed a greater milk yield response (Kung et al, 2003), others did not (Taylor et al, 2002;Arriola et al, 2011b;da Silva et al, 2017). Kleinschmit and Kung (2006) questioned whether the high acetate concentrations of LBinoculated forages would reduce DMI.…”
Section: Performance Of Dairy Cowsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of feeding silage treated with LB on performance of dairy cows in the literature have been inconsistent. Although some studies have observed a greater milk yield response (Kung et al, 2003), others did not (Taylor et al, 2002;Arriola et al, 2011b;da Silva et al, 2017). Kleinschmit and Kung (2006) questioned whether the high acetate concentrations of LBinoculated forages would reduce DMI.…”
Section: Performance Of Dairy Cowsmentioning
confidence: 99%
“…However, this has not been consistently supported in dairy cow studies. Several studies reported that LB did not affect intake (Taylor et al, 2002;Kung et al, 2003;Arriola et al, 2011b) or milk yield (Taylor et al, 2002;da Silva et al, 2017), whereas others reported an increase in milk yield (Kung et al, 2003;Ben-Meir et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Currently, most of LAB inoculants for ensiling were isolated from plant-derived materials, including fresh forage, silage, and so on (Zhang et al, 2015(Zhang et al, , 2018Ni et al, 2017b;Wang et al, 2017). However, plant-derived LAB inoculants sometimes cannot improve animal performance (Kristensen et al, 2010;Santos et al, 2017;Silva et al, 2017). For example, Khota et al (2017) reported that although LAB from sweet corn stover silage could improve the silage quality, it did not show positive effect on in vitro dry matter (DM) digestibility and gas production (GP) of beef cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Corn (Zea mays L.) is a species that stands out for silage production because of its high nutritional value, suitable dry matter (DM) content, high concentration of fermentable carbohydrates, low buffering capacity and high digestibility [3]. However, corn silages, due to the high concentrations of water-soluble carbohydrates (WSC), afford a high content of lactic acid that causes a sharp drop in pH below 3.8, which allows the yeast's development that deteriorates the silage in a short time with exposure to air [4], and because these microorganisms are facultative anaerobic leaven, the residual soluble sugars and also yeasts are able to assimilate lactate, starting aerobic deterioration [3,[5][6][7]. According to [8], the corn plant may have 3 to 5 log cfu/g epiphytic yeasts and the low concentration of fermentation products with antifungal capacity compromises the silage's aerobic stability [9,10].…”
Section: Introductionmentioning
confidence: 99%